PENGARUH KESELAMATAN, KESEHATAN KERJA DAN PENDIDIKAN PELATIHAN TERHADAP KINERJA KARYAWAN MIGAS - Vivi Lusia dan Nurhasanah (Jurnal Manajemen FE-UB, 2016)
This study aims to determine the extent to which the Employee's knowledge of Occupational Safety and Health (K3) in seeking Zero Accident, the provision of Training Education to ensure all employees are able to work safely and committed to work with integrity every time.The data used in this study is Primary data obtained directly by dividing the questionnaire to employees who have worked at least 1 year. The results showed that all variables Occupational Safety and Health (K3) and Training Education (Training) have a significant effect on Employee Performance. Keywords: Effect of Occupational Safety and Health (K3) & Training Education on Performance of Oil and Gas Employees